Efficacy analysis and prediction in phase II clinical trials of non-small cell Lung Cancer - Hoque, Ismoth Ara (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.